1983
DOI: 10.1017/s0022172400060022
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of enrichment media for the isolation of salmonellae from seagull cloacal swabs

Abstract: SUMMARYThe relative efficiency of three selective enrichment broths (Muller-Kauffmann tetrathionate, Rappaport's and selenite F) was investigated for the isolation of salmonellae from seagull cloacal swabs. Pre-enrichment in buffered peptone water was employed throughout the study, which involved the examination of 560 gulls, sixty (10-7%) of which were found to be carrying salmonellae. Rappaport's broth as modified by Vassiliadis for incubation at 43 'C (Vassiliadis et al. 1976) yielded the highest number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The findings concerning the R25 medium were confirmed by Harvey, Price & Xirouchaki (1979), Harvey & Price (1981, 1982a and Fricker, Girdwood & Munro (1983). On the other hand, Alcaide et al (1982), using RV medium with the addition of novobiocin and van Schothorst & Renaud (1983), using RV medium made with soya peptone showed that the RV medium was significantly more efficient than selenite broth or Muller-Kauffmann tetrathionate broth (MK-ISO), respectively.…”
Section: Introductionmentioning
confidence: 81%
“…The findings concerning the R25 medium were confirmed by Harvey, Price & Xirouchaki (1979), Harvey & Price (1981, 1982a and Fricker, Girdwood & Munro (1983). On the other hand, Alcaide et al (1982), using RV medium with the addition of novobiocin and van Schothorst & Renaud (1983), using RV medium made with soya peptone showed that the RV medium was significantly more efficient than selenite broth or Muller-Kauffmann tetrathionate broth (MK-ISO), respectively.…”
Section: Introductionmentioning
confidence: 81%
“…In a previous study (Fricker et al 1983) RV medium was shown to be superior to R25 for the isolation of salmonellas from seagull cloaca1 swabs. In support of these findings this study has demonstrated the superior efficiency of RV over R25 ( P i 0.05) for isolating salmonellas from seagull intestinal material and polluted water.…”
Section: Discussionmentioning
confidence: 92%
“…Many studies (Vassiliadis et al 1978(Vassiliadis et al , 1984Fricker et al 1983;Fricker 1984b) have report-* Present address: Department of Microbiology, University of Reading, London Road, Reading RG1 5AQ, UK. ed that the RV medium is as efficient or is more efficient than R25 medium (Vassiliadis et al 1970), although Harvey & Price (1983) suggested that R25 was the better of the two media when used for the isolation of salmonellas from polluted water.…”
mentioning
confidence: 99%
“…In a recent article (Fricker, Girdwood & Munro, 1983) the choice of enrichment medium was shown to affect significantly the likelihood of isolating salmonellae from seagull cloacal swabs, thus confirming the findings of others working with a variety of samples (Vassiliadis et al 1977(Vassiliadis et al , 1978(Vassiliadis et al , 1979a(Vassiliadis et al , 1981Harvey & Price, 1981;Harvey, Price & Xirouchaki, 1979). In order to develop a standard procedure for the isolation of salmonellae from seagull faecal material, it was considered necessary to investigate the effectiveness of various selective agars in recovering salmonellae after pre-enrichment in buffered peptone water and enrichment in the RB 10 form of Rappaport's broth (Rappaport, Konforti & Navon, 1956;Vassiliadis et al 1976a).…”
Section: Introductionmentioning
confidence: 99%